Stabilization of Patimban Marine Soft Clay with Portland Composite Cement: The Effect of Initial Water Content Variations on Soil Bearing Strength - Pandiangan, Yosse Triade; Cikmit, Arlyn Aristo; Anindita, Listya Diah; Tsuchida, Takashi; Aoyama, Tatsuru (Indonesian Geotechnical Journal, 2026)
Marine clay soil generally exhibits poor physical and mechanical properties, such as high plasticity, low bearing capacity, and excessive settlement under pressure. Soil improvement techniques, such as cement stabilization are thus needed to enhance these characteristics. This study investigates the effect of clay water to cement content ratio (wc/c) and curing time variations on the unconfined compressive strength (qu) of Patimban dredged marine clay stabilized with Portland Composite Cement. Laboratory tests employed variations in ratio of initial water content to its liquid limit (w0/LL), i.e., 1, 1.25, 1.5, and 2, as well as variations in cement content of 20% and 30% of the dry soil mass. Unconfined compressive strength (UCS) test was carried out at curing periods of 1, 3, 7, 28, and 56 days. The peak effective cement hydration process occurred in the first 7 days. The results revealed an inverse correlation between the  ratio and , where an increase in the  ratio caused a decrease in the  values. The high-water content resulted in large voids between cement-soil particles, weakening the strength of the binder. The relationship between the  ratio and the  value indicated a good match yielded an R² value of 0.88-0.94. Further, the unconfined compressive strength of the soil continued to develop with the increasing curing time of 1-56 days. The Average Normalized Difference (A.N.D) value obtained from the relationship between the measured and the estimated compressive strength value was low (11.40%), meaning the estimation equation can be effectively used to estimate the compressive strength of marine clay soil stabilized with Portland Composite Cement at various curing times.